Computational finite element model updating tool for modal testing of structures - Sahin, Abdurrahman; Bayraktar, Alemdar (TECHNO-PRESS, 2014)
In this paper, the development of a new optimization software for finite element model updating of engineering structures titled as FemUP is described. The program is used for computational FEM model updating of structures depending on modal testing results. This paper deals with the FE model updating procedure carried out in FemUP. The theoretical exposition on FE model updating and optimization techniques is presented. The related issues including the objective function, constraint function, different residuals and possible parameters for FE model updating are investigated. The issues of updating process adopted in FemUP are discussed. The ideas of optimization to be used in FE model updating application are explained. The algorithm of Sequential Quadratic Programming (SQP) is explored which will be used to solve the optimization problem. The possibilities of the program are demonstrated with a three dimensional steel frame model. As a result of this study, it can be said that SQP algorithm is very effective in model updating procedure.
Keywords: finite element model updating; optimization; experimental modal analysis; operational modal analysis; SignalCAD; ModalCAD; FemUP; MATLAB; SQP algorithm; OPTIMIZATION TECHNIQUE; ENGINEERING STRUCTURES; DAMAGE IDENTIFICATION; BRIDGE; PARAMETERS; SOFTWARE; Engineering